2018
DOI: 10.3390/ijms19061821
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases in Intellectual Disability: From Genetics to Therapeutic Opportunities

Abstract: Rho-class small GTPases are implicated in basic cellular processes at nearly all brain developmental steps, from neurogenesis and migration to axon guidance and synaptic plasticity. GTPases are key signal transducing enzymes that link extracellular cues to the neuronal responses required for the construction of neuronal networks, as well as for synaptic function and plasticity. Rho GTPases are highly regulated by a complex set of activating (GEFs) and inactivating (GAPs) partners, via protein:protein interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 230 publications
(329 reference statements)
0
55
0
1
Order By: Relevance
“…The dysregulation of those proteins is widely implicated in ID. It was indeed reported that in most pathological cases, RhoA is hyperactivated (Ramakers et al, 2012;Zamboni et al, 2018), although some cases of ID rather show a hypo-activation of the RhoA/ROCK/MLC2 pathway (Kutsche et al, 2000;Ravindran et al, 2017). These data indicate that this pathway, when unbalanced, leads to a pathological state.…”
Section: Rhoa/rock/mlc2 Pathway Dysregulation In Astrocytes In Idmentioning
confidence: 78%
See 1 more Smart Citation
“…The dysregulation of those proteins is widely implicated in ID. It was indeed reported that in most pathological cases, RhoA is hyperactivated (Ramakers et al, 2012;Zamboni et al, 2018), although some cases of ID rather show a hypo-activation of the RhoA/ROCK/MLC2 pathway (Kutsche et al, 2000;Ravindran et al, 2017). These data indicate that this pathway, when unbalanced, leads to a pathological state.…”
Section: Rhoa/rock/mlc2 Pathway Dysregulation In Astrocytes In Idmentioning
confidence: 78%
“…Several identified genes implicated in XLID are involved in the regulation of the RhoGTPases (Ba, van der Raadt, & Nadif Kasri, 2013;Zamboni et al, 2018), which are small GTPase proteins of the Rho family that play a critical role in cytoskeleton remodeling. They regulate different cellular processes such as migration, adhesion and morphology (Etienne-Manneville & Hall, 2002;Raftopoulou & Hall, 2004;Ridley, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…GRIA3 (OMIM *305915), on the other hand, is part of the α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole acid (AMPA) glutamate receptor. These scaffolding proteins are the core of the synapse because they translate upstream signals from CAM and receptors to changes in gene expression or cytoskeleton organization …”
Section: Molecular and Cellular Pathways Involved In Idmentioning
confidence: 99%
“…Disruption of PAK‐Arp2/3 function leads to defective synaptic plasticity and learning deficits in association with intellectual disability . Other studies show that PAK3 gene mutations, that disrupt kinase activation or function, cause X‐linked intellectual disability . Reduced regional PAK levels are described for AD brains , and decreased PAK expression in a triple transgenic AD mouse model has been associated with dendrite and spine defects .…”
Section: Introductionmentioning
confidence: 99%